Clinical and Analytical Performance of a Novel Point-of-Care High-Sensitivity Cardiac Troponin I Assay - Koechlin, Luca; Boeddinghaus, Jasper; Lopez-Ayala, Pedro; Reber, Cornelia; Nestelberger, Thomas; Wildi, Karin; Spagnuolo, Carlos C; Strebel, Ivo; Glaeser, Jonas; Bima, Paolo; Crisanti, Luca; Herraiz-Recuenco, Lourdes; et al. (Journal of the American College of Cardiology, 2024)
BACKGROUND: Point-of-care (POC) high-sensitivity cardiac troponin assays may further accelerate the diagnosis of myocardial infarction (MI). OBJECTIVES: This study sought to assess the clinical and analytical performance of the novel high-sensitivity cardiac troponin I (hs-cTnI)-SPINCHIP POC test. METHODS: Adult patients presenting with acute chest discomfort to the emergency department were enrolled in an international, diagnostic, multicenter study. The final diagnosis was centrally adjudicated by 2 independent cardiologists using all clinical information. We compared the discriminatory performance of hs-cTnI-SPINCHIP with current established central laboratory assays and derived an assay-specific hs-cTnI-SPINCHIP 0/1-hour algorithm. Secondary analyses included sample type comparisons (whole blood, fresh/frozen plasma, and capillary finger prick) and precision analysis. RESULTS: MI was the adjudicated final diagnosis in 214 (19%) of 1,102 patients. Area under the receiver-operating characteristic curve was 0.94 (95% CI: 0.92-0.95) for hs-cTnI-SPINCHIP vs 0.94 (95% CI: 0.92-0.95) for hs-cTnI-Architect (P = 0.907) and 0.93 (95% CI: 0.91-0.95) for high-sensitivity cardiac troponin T Elecsys (P = 0.305). A cutoff <7 ng/L at presentation (if chest pain onset was >3 hours) or <7 ng/L together with a 0/1-hour delta of <4 ng/L ruled out 51% with a sensitivity and negative predictive value of 100% (95% CI: 97.7%-100%) and 100% (95% CI: 99.0%-100%), respectively. A hs-cTnI-SPINCHIP concentration ≥36 ng/L or a 0/1-hour delta ≥11 ng/L ruled in 27% with a specificity and positive predictive value of 90.9% (95% CI: 88.3%-92.9%) and 72.9% (95% CI: 66.4%-78.6%), respectively. Bootstrap internal validation confirmed excellent diagnostic performance. High agreement was observed between different sample types. CONCLUSIONS: The SPINCHIP hs-cTnI POC test has very high diagnostic accuracy. Its assay-specific 0/1-hour algorithm achieved very high sensitivity/negative predictive value and specificity/positive predictive value for rule-out/in MI. (Advantageous Predictors of Acute Coronary Syndromes Evaluation [APACE] Study [APACE]; NCT00470587).
Keywords: Female; biologické markery; Biomarkers; ženské pohlaví; Troponin I; lidé; Sensitivity and Specificity; senzitivita a specificita; prospektivní studie; Male; Aged; Prospective Studies; Myocardial Infarction; Point-of-Care Systems; vyšetření u lůžka; lidé středního věku; troponin I; senioři; mužské pohlaví; Middle Aged; infarkt myokardu; Humans